A multidisciplinary approach for the emergency care of patients with left ventricular assist devices: A practical guide - Cameli, Matteo; Pastore, Maria Concetta; Mandoli, Giulia Elena; Landra, Federico; Lisi, Matteo; Cavigli, Luna; D'Ascenzi, Flavio; Focardi, Marta; Carrucola, Chiara; Dokollari, Aleksander; Bisleri, Gianluigi; Tsioulpas, Charilaos; et al. (Frontiers in Cardiovascular Medicine, 2022)
Left ventricular assist device (LVAD) utilization as bridge-to-transplantation or destination therapy to support cardiac function in patients with end-stage heart failure (HF) is increasing in all developed Countries. However, the expertise required for implantation and management of patients referred for LVAD treatment remains limited to few reference Centers, often very far from patients’ home. Although patients undergoing LVAD implantation have to permanently refer to the LVAD center for the management and follow-up of the device also after implantation, for routine assistance and urgent health issues, either related to the device or generic, they would refer to the local healthcare service. Therefore, each clinician, from bigger to smaller Centers, should be prepared to manage LVAD-carriers and to the possible risks associated to LVAD management. Particularly, the emergency treatment of patients with LVAD slightly differs from the conventional emergency protocols and requires specific knowledge and a multidisciplinary approach in order to avoid ineffective treatment or dangerous consequences. The aim of this review paper is to provide a standard protocol for the management of emergency and urgency in LVAD patients, elucidating the role of each healthcare professional and the importance of collaboration between emergency department, in-hospital ward and LVAD reference center and also providing algorithms designed to ensure a timely, adequate and effective treatment to these patients.